EFEKTIVITAS DIET TERI TAWAR DAN SUPLEMENTASI KALSITRIOL UNTUK MENCEGAH OSTEOPOROSIS PADA TIKUS OVARIEKTOMI The Effectiveness of Fresh Anchovies Diet and Calcitriol Supplementation to Prevent Osteoporosis in Ovariectomized Rats (The Effectiveness of Fresh Anchovies Diet and Calcitriol Supplementation to Prevent Osteoporosis in Ovariectomized Rats) - H, Hartiningsih; Anggraeni, Devita; S, Sudarminto (Universitas Syiah Kuala, 2016)
This study was conducted to assess the effectiveness of a diet contained fresh anchovies and calcitriol supplementation for 6 weeks to prevent osteoporosis in ovariectomized rats. Fifteen Wistar rats aged 8 weeks were divided randomly into 3 groups (normal/K, ovariectomized/Ov, and ovariectomized + calcitriol/OVD), 5 mice each. Group K and Ov rats were fed with fresh anchovies, while the OVD group was fed with fresh anchovies + calcitriol. At the age of 15 weeks, all mice were done for euthanasia, then left femur was collected for immunohistochemistry examination of tartrate resistant acid phosphatase5b (TRAP5b). The detection of (TRAP5b) was conducted using a monoclonal ant ibody anti TRAP5b, and detected using a streptavidin-biotin. The results showed that the metaphysis part of distal femur bone of mice group K, Ov, and OVD were positive TRAP5b stained with brown color on trabecular bone in bone marrow cavity and trabecular spiculum surface, but rats in group K and Ov had extensive bone marrow cavity and normal trabecular spiculum, whereas OVD group showed bone marrow cavity dilation, accumulation of adipocytes in the bone marrow cavity, and shorter the spiculum of trabeculae. It can be concluded that fresh anchovies diet and calcitriol supplementation for 6 weeks are not effective in preventing osteoporosis in ovariectomized rats.Key words: calcitriol, femur, ovariohisterectomy